2011
DOI: 10.1016/j.rbmo.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Methodology matters: IVF versus ICSI and embryonic gene expression

Abstract: The use of assisted reproduction treatment, especially intracytoplasmic sperm injection (ICSI), is now linked to a range of adverse consequences, the aetiology of which remains largely undefined. The objective was to determine differences in gene expression of blastocysts generated by ICSI as well as ICSI with artificial oocyte activation (ICSI-A) versus the less manipulative IVF, providing fundamental genetic information that can be used to aid in the diagnosis or treatment of those adversely affected by assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…In human ART, concerns remain about whether fertilization techniques influence the distribution and expression of key transcription factors responsible for the developmental program of embryogenesis [7,22,51]. One of them, the POU-family transcription factor Oct4, is expressed throughout early embryonic development and becomes progressively restricted first to the entire inner cell mass (ICM) and then to the epiblast (EPI) at the blastocyst stage [35,46].…”
Section: Discussionmentioning
confidence: 99%
“…In human ART, concerns remain about whether fertilization techniques influence the distribution and expression of key transcription factors responsible for the developmental program of embryogenesis [7,22,51]. One of them, the POU-family transcription factor Oct4, is expressed throughout early embryonic development and becomes progressively restricted first to the entire inner cell mass (ICM) and then to the epiblast (EPI) at the blastocyst stage [35,46].…”
Section: Discussionmentioning
confidence: 99%
“…Particular challenges arise from patients exhibiting high intra-and intervariability (Feuerstein et al, 2012;Maston et al, 2006;Sapey et al, 2008) and variations in gene expression, which have been linked to a number of patient and treatment characteristics (Bridges et al, 2011;Wathlet et al, 2011). Consequently, some biomarkers indicated as strong predictors of developmental potential in specific patient populations may not be appropriate to select between embryos in other patient populations or even between embryos produced by the same individual.…”
Section: Analysis Of Transcriptomementioning
confidence: 99%
“…For example, IVF-produced morulae in the domestic cat display higher relative levels of Dnmt1 mRNA than do ICSI morulae (Waurich et al, 2010). Similarly, all reports in mice indicate that the global gene expression profiles differ significantly among blastocysts derived from ICSI versus IVF (Bridges et al, 2011;Kohda et al, 2011); ICSI followed by artificial oocyte activation versus IVF and ICSI, respectively (Bridges et al, 2011); and ICSI versus in vivo development (Giritharan et al, 2010). Interestingly, Kohda et al (2011) showed that in mice, the relative changes in ICSI-versus IVF-associated transcriptomes observed at the blastocyst stage remain at the neonatal stage, but disappear at 8-weeks of age.…”
Section: Intracytoplasmic Sperm Injectionmentioning
confidence: 93%